Staphylococcus epidermidis Boosts Innate Immune Response by Activation of Gamma Delta T Cells and Induction of Perforin-2 in Human Skin - Pastar, Irena; O’Neill, Katelyn; Padula, Laura; Head, Cheyanne R.; Burgess, Jamie L.; Chen, Vivien; Garcia, Denisse; Stojadinovic, Olivera; Hower, Suzanne; Plano, Gregory V.; Thaller, Seth R.; Tomic-Canic, Marjana; et al. (Frontiers in Immunology, 2020)
Perforin-2 (P-2) is an antimicrobial protein with unique properties to kill intracellular bacteria. Gamma delta (GD) T cells, as the major T cell population in epithelial tissues, play a central role in protective and pathogenic immune responses in the skin. However, the tissue-specific mechanisms that control the innate immune response and the effector functions of GD T cells, especially the cross-talk with commensal organisms, are not very well understood. We hypothesized that the most prevalent skin commensal microorganism, Staphylococcus epidermidis, may play a role in regulating GD T cell-mediated cutaneous responses. We analyzed antimicrobial protein P-2 expression in human skin at a single cell resolution using an amplified fluorescence in situ hybridization approach to detect P-2 mRNA in combination with immunophenotyping. We show that S. epidermidis activates GD T cells and upregulates P-2 in human skin ex vivo in a cell-specific manner. Furthermore, P-2 upregulation following S. epidermidis stimulation correlates with increased ability of skin cells to kill intracellular Staphylococcus aureus. Our findings are the first to reveal that skin commensal bacteria induce P-2 expression, which may be utilized beneficially to modulate host innate immune responses and protect from skin infections.